The Talmud, the Hippocratic Corpus and Mark’s healing Jesus on infectious diseases - Dube, Zorodzai (Hervormde teologiese studies, 2018)
Through interacting with the sick, did Jesus contract infectious diseases or did he take preventive herbs to avoid them? During biblical times, infectious diseases were fatal. Diarrhoea, cough, pneumonia and skin diseases would quickly spread across villages or cities. Underscoring the seriousness with which prevention of infectious diseases was taken, 213 of the 613 biblical commandments concern hygiene. This study has two tasks: firstly, exploring the various techniques undertaken to avoid infectious diseases by looking at daily preventive hygienic activities. Secondly, given that Jesus was always in the company of sick crowds, the study re-describes Mark 1:4–45, where Jesus, after healing the leper, was forbidden from entering the city as indicative of fear against infectious diseases. Furthermore, the story (Mk 3:7–12) whereby Jesus requested a boat to create a gap between himself and the people is plausible from the perspective of infectious diseases.